(untitled) (Research, Society and Development, 2021)
Kefir is considered a probiotic food due to the benefits associated with its consumption, such as immune system stimulation, intestinal microbiota balance and antimicrobial activity against pathogens. Thus, the food industry has been adapting to the new trend by stimulating the development of functional foods. Thereby, the present study aims to evaluate the microbiological and physicochemical characteristics of plum and coconut blancmange made with Kefir In the microbiological analysis were analyzed coliforms; Salmonella, molds counting, yeasts and lactobacilli (Silva et al., 2007) and for the physicochemical analyzes were analyzed pH, oBrix, titratable acidity, fat content, lactose, calcium and total solids (Brasil, 2005). A decrease in pH from 4.21 to 4.12 was observed in the blancmange an increase in acidity from 1.095 to 1.185%, due to the production of organic acids during alcoholic fermentation and a decrease in °Brix from 24.67 to 21.67. In addition, it had a fat content of 8.51%, calcium content of 0.159%, lactose content of 2.805% and total solids content of 0.679%. It was noted that the lactose content remained high due to the low concentration of Kefir grains. In microbiological analysis there was no presence of coliforms and salmonella thus ensuring the sanitary hygiene of the product. The molds and yeasts counting were also within the expected parameters between 8x103 to 3. 5x104 CFU/g. It was noticed that the initial amount of lactobacilli decreased over the days, reaching 0 and losing the functional food proposition. It is therefore concluded that it is necessary to reformulate this product with a larger amount of kefir to obtain a lower lactose content.